The Effectiveness of Mindfulness-Based Therapy on Reducing Stress and Improving Emotion Regulation in Patients with Post-Traumatic Stress Disorder (PTSD) - Zadfallah Farshami, Hanieh; Bozorgi, Masoome (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Post-Traumatic Stress Disorder (PTSD) is a significant challenge in the field of mental health, requiring effective and sustainable interventions. Methods and Materials: This study aimed to examine the effectiveness of mindfulness-based therapy in reducing stress and improving emotion regulation in clients with PTSD. The statistical population included clients with PTSD who visited counseling and psychological services centers in Rasht in 2024. From this population, 30 individuals were selected through convenience sampling and divided into experimental and control groups (15 people in each group). The instruments used included the PTSD Checklist (PCL-5), the Perceived Stress Scale (PSS), and the Emotion Regulation Questionnaire (ERQ). Data analysis was performed using SPSS version 26 and statistical methods such as independent t-test, multivariate analysis of variance (MANOVA), and Pearson correlation analysis. Findings: The results indicated that mindfulness-based therapy significantly reduced stress and improved emotion regulation in clients with PTSD. Conclusion: These findings were consistent with previous studies and demonstrated that mindfulness-based therapy could be used as an effective and sustainable method for managing PTSD symptoms. However, limitations such as a limited statistical population, relatively small sample size, and the use of self-report questionnaires should be considered in future research. Suggestions for future research include conducting studies with larger samples and longer follow-up periods, combining mindfulness-based therapy with other therapeutic methods, and using more objective assessment tools.